2016
DOI: 10.1136/tobaccocontrol-2015-052633
|View full text |Cite
|
Sign up to set email alerts
|

Toxicant exposure from smoking a little cigar: further support for product regulation

Abstract: The results support the notion that regulation of little cigars is appropriate in light of public health considerations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
57
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(60 citation statements)
references
References 50 publications
3
57
0
Order By: Relevance
“…Importantly, we found that exhaled CO levels significantly increased following cigar smoking in all groups. These findings confirm previous reports in dual cigar and cigarette smokers, 810,12,20,36 suggesting that many cigar smokers are exposed to significant levels of CO. Importantly, even self-reported non-inhalers had small, yet significant, increases in exhaled CO, perhaps indicative of mild smoke inhalation.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Importantly, we found that exhaled CO levels significantly increased following cigar smoking in all groups. These findings confirm previous reports in dual cigar and cigarette smokers, 810,12,20,36 suggesting that many cigar smokers are exposed to significant levels of CO. Importantly, even self-reported non-inhalers had small, yet significant, increases in exhaled CO, perhaps indicative of mild smoke inhalation.…”
Section: Discussionsupporting
confidence: 92%
“…Cigar smoking significantly reduced QSU-B and MNWS scores, as previously reported, 8,10,11 suggesting that cigar smoking confers some benefit for reducing the negative symptoms associated with withdrawal.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations